Partial discharge in medium and high voltage electrical devices - S. Balasubramaniam, Yogendra; Talib, Mohd Aizam; Ishak, Sanuri; Avinash Raj, Avinash Raj; Mohd Amir, Mohd Dzaki; Abdul Aziz, Mohd Azhar; Mohd Yousof, Mohd Fairouz (Penerbit UTHM, 2020)
Partial discharges (PD) are small electrical sparks or pulses that occur within the insulation of medium and high voltage electrical devices. These pulses will partially bridge the gap between phase insulation to ground or phase to phase insulation. These discharges erode insulation and eventually result in insulation failure. There are three types of discharges for insulation that are internal discharges, corona and surface discharge.